2021
DOI: 10.1021/acssensors.1c01258
|View full text |Cite
|
Sign up to set email alerts
|

Substitutional Doping of MoS2 for Superior Gas-Sensing Applications: A Proof of Concept

Abstract: Two-dimensional layered materials (like MoS 2 and WS 2 ) those are being used as sensing layers in chemoresistive gas sensors suffer from poor sensitivity and selectivity. Mere surface functionalization (decorating of material surface) with metal nanoparticles (NPs) might not improve the sensor performance significantly. In this respect, doping of the layered material can play a significant role. Here, we report a simple yet effective substitutional doping technique to dope MoS 2 with noble metals. Through var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 43 publications
0
47
0
Order By: Relevance
“…These results indicated that, irrespective of the method of preparation of a monolayer or a few layers, the sensors so obtained have several drawbacks. These include slow charge transfer and poor performance under high-humidity conditions, which limit their gas detection performance. , Subsequent to that, methodologies for altering the physical or chemical properties of pure MoSe 2 , such as noble-metal doping and heterostructure fabrication, have been examined. ,,, Unfortunately, enhancing the reactivity of sensing materials toward gases or VOCs via noble-metal catalysis decoration does not really improve the sensing surface activities . Furthermore, the scarcity and higher cost of noble metals limit their widespread application .…”
Section: Introductionmentioning
confidence: 99%
“…These results indicated that, irrespective of the method of preparation of a monolayer or a few layers, the sensors so obtained have several drawbacks. These include slow charge transfer and poor performance under high-humidity conditions, which limit their gas detection performance. , Subsequent to that, methodologies for altering the physical or chemical properties of pure MoSe 2 , such as noble-metal doping and heterostructure fabrication, have been examined. ,,, Unfortunately, enhancing the reactivity of sensing materials toward gases or VOCs via noble-metal catalysis decoration does not really improve the sensing surface activities . Furthermore, the scarcity and higher cost of noble metals limit their widespread application .…”
Section: Introductionmentioning
confidence: 99%
“… 1 4 Key advantages of these interfaces are represented by their high surface-to-volume ratios, 5 the direct-to-indirect band gap transition, 6 , 7 the occurrence of chemical terminations like edges, boundaries, and surface vacancies, 8 10 and the engineered functionalities by metal nanoparticle decoration or substitutional doping. 11 , 12 Despite these features, a substantial disadvantage of TMDs and MCs, adversely affecting sensors’ signal reproducibility, is represented by their intrinsic thermodynamic instability (Δ G < 0), leading to spontaneous oxidation in dry-/wet-air laboratory conditions. 13 , 14 In details, the displacement of sulfur, selenium, and tellurium atoms, operated by ambient O 2 in MoS 2 and WS 2 sulfides, 15 , 16 MoSe 2 , WSe 2 , InSe, GaSe, and SnSe 2 selenides, 17 − 20 and MoTe 2 and WTe 2 21 , 22 tellurides, stimulates the nucleation over step edges of amorphous oxidized states, which proceeds through basal planes, eventually passivating all the flake’s surface.…”
mentioning
confidence: 99%
“…Two-dimensional (2D) layered transition metal dichalcogenide (TMD) and metal chalcogenide (MC) semiconductors, with near atomic-scale thickness, have been extensively proposed in the past decade as alternative materials for traditional nanocrystalline metal oxides (MO) for gas sensing applications. Key advantages of these interfaces are represented by their high surface-to-volume ratios, the direct-to-indirect band gap transition, , the occurrence of chemical terminations like edges, boundaries, and surface vacancies, and the engineered functionalities by metal nanoparticle decoration or substitutional doping. , Despite these features, a substantial disadvantage of TMDs and MCs, adversely affecting sensors’ signal reproducibility, is represented by their intrinsic thermodynamic instability (Δ G < 0), leading to spontaneous oxidation in dry-/wet-air laboratory conditions. , In details, the displacement of sulfur, selenium, and tellurium atoms, operated by ambient O 2 in MoS 2 and WS 2 sulfides, , MoSe 2 , WSe 2 , InSe, GaSe, and SnSe 2 selenides, and MoTe 2 and WTe 2 , tellurides, stimulates the nucleation over step edges of amorphous oxidized states, which proceeds through basal planes, eventually passivating all the flake’s surface. This phenomenon is further enhanced when the sensor’s operating temperature (OT) is increased in the range of 25–150 °C to compensate for irreversible adsorption of gas molecules, as frequently experienced in metal oxide and 2D layered sensors. , …”
mentioning
confidence: 99%
“…Significant improvement in sensing performance of various 2D dichalcogenides over surface functionalization with suitable metal nanoparticles has been reported elsewhere. [ 57 ] Following this, we have doped GPM with selected dopants (Ag, Cu, Zn) separately, which results into the formation of Ag@GPM, Cu@GPM, and Zn@GPM, respectively. The formation energies ( E f ) of these substitutions are calculated to be −2.6, −4.8, and −1.8 eV for Ag@GPM, Cu@GPM, and Zn@GPM, respectively.…”
Section: Resultsmentioning
confidence: 99%